2015
DOI: 10.1007/s12640-015-9550-z
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Compound ITC-3 Activates the Nrf2 Signaling and Provides Neuroprotection in Parkinson’s Disease Models

Abstract: Parkinson's disease (PD) is a progressive neurodegenerative disorder accompanied by a selective loss of the dopamine(DA)ergic neurons residing in the substantia nigra. There is ample evidence that neuroinflammation and oxidative stress are involved in the pathogenesis of PD. In the present study, we aimed at protecting the DAergic neurons by suppressing these cellular events and generated a novel synthetic isothiocyanate ITC-3. The compound led to elevation of nuclear and total levels of the transcription fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…For example, MPTP‐treated Nrf2 knockout mice exhibited increased levels of inflammatory markers such as cyclooxygenase‐2, inducible NO synthase, IL‐6, and TNF‐α, and are prone to neuroinflammation (Rojo et al, 2010). Activation of Nrf2 signaling by a novel compound ITC‐3 inhibited oxidative stress and inflammation, abolished motor deficits and provided neuroprotection in a MPTP‐elicited animal model of PD (Lee et al, 2015). Hydralazine and protocatechuic aldehyde exerted neuroprotection in MPTP‐ or MPP + ‐induced PD models at least partially by activation of Nrf2 pathway (Guo et al, 2019; Guo et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…For example, MPTP‐treated Nrf2 knockout mice exhibited increased levels of inflammatory markers such as cyclooxygenase‐2, inducible NO synthase, IL‐6, and TNF‐α, and are prone to neuroinflammation (Rojo et al, 2010). Activation of Nrf2 signaling by a novel compound ITC‐3 inhibited oxidative stress and inflammation, abolished motor deficits and provided neuroprotection in a MPTP‐elicited animal model of PD (Lee et al, 2015). Hydralazine and protocatechuic aldehyde exerted neuroprotection in MPTP‐ or MPP + ‐induced PD models at least partially by activation of Nrf2 pathway (Guo et al, 2019; Guo et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, knockdown of Keap1 increases the resistance to rotenone in cortical cultures (52). A recent study demonstrated that the activation of Nrf2 signaling by a novel compound ITC-3 inhibits oxidative stress and abolishes PD-associated motor deficits in an animal model of PD (13). In this study, we found that safranal could inhibit Keap1 expression induced by rotenone and promoted Nrf2 nuclear accumulation that led to transcription of antioxidant gene expression, by which safranal alleviated rotenone-induced neurotoxicity in dopaminergic neurons.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has suggested that the Keap1/Nrf2 signaling plays an important role in neurodegenerative diseases including PD (12). The activation of Nrf2 signaling shows a protective effect against PD (13).…”
Section: Introductionmentioning
confidence: 99%
“…These promising results obtained with natural ITCs in different model of PD led to the production of synthetic ITCs to be investigated in this context of neurodegeneration. Lee et al [149] reported the synthesis of three novel ITCs (ITC-1, ITC-2, and ITC-3) and investigated their protective effects both in vitro, using CATH.a neuronal cells and microglial BV-2 cells, and in vivo in an animal model of PD. ITC-3 demonstrated the highest performance thanks to its low cytotoxicity compared to ITC-1, ITC-2, and SF.…”
Section: Parkinson's Diseasementioning
confidence: 99%